Habitual Scrolling and the Decline in Critical Thinking Skills in the Social Media Era: A Qualitative Study from a Communication Studies Perspective - Riza Ramlan (International Journal Labs, 2026)
The rapid development of digital communication technologies has significantly transformed the way individuals’ access and consume information, particularly through social media platforms. One emerging phenomenon is habitual scrolling, a repetitive and often unconscious activity that enables users to continuously consume large amounts of content. This study aims to explore how habitual scrolling practices influence users’ critical thinking skills in evaluating digital information. Using a qualitative research approach, data were collected through in-depth interviews, observations, and documentation involving 5–10 active social media users aged 18–35 years. The findings reveal that habitual scrolling has become an integral part of daily routines, often performed without clear purpose and driven by platform features such as infinite scrolling and algorithmic recommendations. This behaviour leads to rapid and superficial information consumption, where users tend to skim content rather than engage deeply. Consequently, the ability to critically evaluate information decreases, as users rarely verify sources or reflect on content before accepting or sharing it. The study concludes that habitual scrolling contributes to a decline in critical thinking by promoting fast, intuitive processing over analytical reasoning. Therefore, enhancing digital literacy and encouraging mindful media use are essential to mitigate its negative cognitive impacts.